Blended learning via YouTube media to Motivate EFL learners on speaking skill - Eva Fachriyah; Erma Perwitasari (Loquen, 2020)
This study aims to investigate language teaching in the practice of English speaking skills through blended learning, utilizing Youtube as a media. Participants were 42 (males and female) in third semester students enrolled in the second year in Information Technology program, Serang Raya University. The method was classroom action research. Data collected through the procedure taken from the Kemmis Taggart model. Those were begun from planning, action, observation, and reflection. Meanwhile, the data analyzed based on the whole observation of the action on each circle and the result of questionnaires. The result shows that students were greatly motivated on practicing speaking skills.